Physical efficiency of girls of 9-10 years in the process of physical training aimed at developing endurance - Samokih I.I (Kharkov National Pedagogical University, 2012)
Essence of specific of evaluation of physical capacity opens up in physical education of girls. In researches 45 girls took part in age 9-10 years. In a pedagogical experiment registered the indexes of physical development, physical preparedness, physical capacity. Expedience of the use of the offered method is grounded in physical education in schools. It is shown that in the process of double employments by a physical culture with priority implementation of exercises on endurance the level of physical capacity of schoolgirls rises considerably. Directions of prognostication of the state of physical health of schoolboys and correction of process of physical education are recommended at school.